Pengembangan Sistem Kontrol Navigasi Kursi Roda Cerdas Menggunakan Arsitektur Subsumption Studi Kasus Door Passing Dan Corridor Following - Setiawan, Iwan; Darjat, Darjat; Gusman Namara, Rano (Departemen Teknik Elektro, Universitas Diponegoro, 2008)
Several research have shown that both children and adults benefit substantially from access to a means of independent mobility. While the needs of many individuals with disabilities can be satisfied with traditional manual wheelchairs, a segment of the disabled community finds it difficult or impossible to use wheelchairs independently. To accommodate this population, researchers have used technologies originally developed for mobile robots to create